(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article which focuses on the life and work of Archbishop Robert Leighton begins with a brief biography. It contains transcriptions of entries from the Dalkeith presbytery books and Session records of Newbattle parish in which Leighton is referenced, with particular focus on the times that he was absent from his parish to visit his elderly father. Also included are transcriptions of some official letters that he may have contributed to. Meeting notes for 12 May, 1862 are appended.